2008
DOI: 10.1002/ejoc.200800796
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Stereodivergent Syntheses of D‐ and L‐Fagomines and Their Analogues

Abstract: The syntheses of D-and L-fagomines 1, 4, 5 and 6 and their isomers from starting D-glycals have been achieved. The syntheses involve elaboration of common amino alcohol precursors obtained from 2-deoxy-1-amino sugar derivatives. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…8e10 For instance, they can be prepared by formation of 2-iodo-2-deoxyglycoside, followed by dehalogenation. 8 Likewise, similar procedures also include the formation of 2-chloro-2-deoxyglycoside and subsequent radical dechlorination, 9 as well as the preparation of 2-deoxy-2-phenylthio-glycoside followed by the reduction of Raney Nickel. 10 Previous reports indicated that acid-catalyzed addition to glycals represents the most direct method that can be operated under various conditions, including hydrogen bromide, 11 triphenylphosphine hydrogenbromide, 12 Dowex-50 [H þ ] in the presence of LiBr, 13 CeCl 3 $7H 2 O/NaI, 14 LaCl 3 $7H 2 O/NaI, 15 TMSOTfeNEt 3 , 16 BCl 3 (or BBr 3 ), 17 ceric ammonium nitrate, 18 GaCl 3 ,19 and Rhenium(V) [ReOCl 3 (SMe 2 )(OPPh 3 )].…”
Section: Introductionmentioning
confidence: 98%
“…8e10 For instance, they can be prepared by formation of 2-iodo-2-deoxyglycoside, followed by dehalogenation. 8 Likewise, similar procedures also include the formation of 2-chloro-2-deoxyglycoside and subsequent radical dechlorination, 9 as well as the preparation of 2-deoxy-2-phenylthio-glycoside followed by the reduction of Raney Nickel. 10 Previous reports indicated that acid-catalyzed addition to glycals represents the most direct method that can be operated under various conditions, including hydrogen bromide, 11 triphenylphosphine hydrogenbromide, 12 Dowex-50 [H þ ] in the presence of LiBr, 13 CeCl 3 $7H 2 O/NaI, 14 LaCl 3 $7H 2 O/NaI, 15 TMSOTfeNEt 3 , 16 BCl 3 (or BBr 3 ), 17 ceric ammonium nitrate, 18 GaCl 3 ,19 and Rhenium(V) [ReOCl 3 (SMe 2 )(OPPh 3 )].…”
Section: Introductionmentioning
confidence: 98%
“…In continuation of our interest in synthesizing structurally diverse sugar derivatives as glycosidase inhibitors, we herein wish to report a stereoselective synthesis of an imino glycal. Further, we also report on the utility of the imino glycal in the synthesis of (–)‐1‐ epi ‐adenophorine, and a homoiminosugar and report its glycosidase inhibition activity.…”
Section: Introductionmentioning
confidence: 99%
“…For diastereodivergent routes to D-and L-fagomines, with potent antihyperglycemic effect and having potentiation of glucose-induced insulin secretion, 25 a 2-chloroamine obtained from 3,4,6-tri-O-benzyl-D-glucal has been used as common substrate by Vankar and co-workers. 26 The main key features of the synthesis is the cyclization step via a S N 2 reaction in the case of L-()-fagomine, whereas in the other case an intramolecular reductive amination gave the other D-diastereomer (Scheme 16). Using the same divergent routes starting from 3,4,6-tri-O-benzyl-D-galactal, which was transformed into the 2-chloro azasugar, the corresponding L-(+)-and D-(+)-1,2-dideoxy-galactostatins were synthesized as well.…”
Section: Azasugarsmentioning
confidence: 99%